A comprehensive bibliometric analysis of global research on the role of acrolein in Alzheimer’s disease pathogenesis: involvement of amyloid-beta - Jallow, Amadou Wurry; Nguyen, Doan Phuong Quy; Sanotra, Monika Renuka; Hsu, Chun-Hsien; Lin, Yi-Fang; Lin, Yung-Feng (Frontiers in Aging Neuroscience, 2024)
Background Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive and behavioral decline. Acrolein, an environmental pollutant and endogenous compound, is implicated in AD development. This research employs bibliometric analysis to assess current trends and key areas concerning acrolein-AD interaction. Methods The Web of Science was used to extensively review literature on acrolein and AD. Relevant data were systematically gathered and analyzed using VOSviewer, CiteSpace, and an online bibliometric tool. Results We identified 120 English publications in this specialized field across 19 journals. The Journal of Alzheimer’s Disease was the most prominent. The primary contributors, both in terms of scientific output and influence, were the USA, the University of Kentucky, and Ramassamy C, representing countries/regions, institutions, and authors, respectively. In this field, the primary focus was on thoroughly studying acrolein, its roles, and its mechanisms in AD utilizing both in vivo and in vitro approaches. A significant portion of the research was based on proteomics, revealing complex molecular processes. The main focuses in the field were “oxidative stress,” “lipid peroxidation,” “amyloid-beta,” and “cognitive impairment.” Anticipated future research trajectories focus on the involvement of the internalization pathway, covering key areas such as synaptic dysfunction, metabolism, mechanisms, associations, neuroinflammation, inhibitors, tau phosphorylation, acrolein toxicity, brain infarction, antioxidants, chemistry, drug delivery, and dementia. Our analysis also supported our previous hypothesis that acrolein can interact with amyloid-beta to form a protein adduct leading to AD-like pathology and altering natural immune responses. Conclusion This study provides a broad and all-encompassing view of the topic, offering valuable insights and guidance to fellow researchers. These emerging directions underscore the continuous exploration of the complexities associated with AD. The analyses and findings aim to enhance our understanding of the intricate relationship between acrolein and AD for future research.